Impact of European Union's Sanctions on External Economic Relations of Russia - Apostol, Marina; Bolotov, Ilya; Zeynalov, Ayaz; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis assesses the impact and costs of the EU’s sanctions in 2014 and 2022 on the Russian economy. Based on the studied literature and provided literature review, the research question of the thesis is aimed at the assessment of the economic impact of the EU’s sanctions in 2014 and 2022 on Russian trade and bilateral relations with key trade partners with a focus on trade flows in the oil industry. The hypothesis will test whether the EU’s sanctions imposed on Russia in 2014 and 2022 significantly and negatively impacted trade flows in the oil industry which resulted in lost trade for Russia and severe economic costs such as a decrease in GDP, decline in investment flows and bilateral trade volumes and negative development of the economic performance of companies involved. There are three chapters in the thesis. In the first chapter, the author defines what sanctions are, what sanctions’ impact means and formulate methodology and a research gap. In the second chapter, the author focuses on the assessment of the EU’s sanctions of 2014 and 2022 impact on the Russian economy from the internal, external balance, and trade balance points of view, including total trade, key trading partners, and two selected product groups- mineral fuels (SITC 3) and semiconductors (SITC 77637). In the third chapter, the author focuses on the assessment of the EU’s sanctions impact on the Russian oil industry and provides a case study of the selected Russian oil companies such as state-owned companies like Rosneft and Gazpromneft and private companies like Lukoil and Surgutneftgas. Based on the assessment provided, due to the EU's imposed sanctions the economic costs for Russia were major, not severe. The GDP declined more after 2014 than after 2022. The increase in GDP in 2022 was provoked by high global prices, but after the EU introduced the oil price cap, Russian GDP showed a decline in 2023.
As a result, the total Russian government and oil and gas revenues declined in 2023, as did total expenditure. Despite that, the defense expenditure increased. It was also proven that the EU’s sanctions negatively impacted trade flows in the oil industry which resulted in lost total and oil trade for Russia. It proved a decline in the Russian trade balance, a decrease in total exports and imports, as well as a decline in trade volumes with the key trading partners, decreased exports of mineral fuels to the EU countries, and a decline of semiconductors' imports which Russia needs for its high-tech sectors. Moreover, the FDI outflow declined by 120% in Q3 2022 since around 300 global companies left Russia and the EU froze Russian assets abroad. As a result, due to Russian reliance on oil trade, Russia diversified its key trading partners, particularly putting focus on partnerships with BRICS countries, such as China and India. However, the economic costs and impact could not be mitigated due to reliance on bilateral trade with the EU, notably in mineral fuels before the 2022 events. However, Russia started to practice parallel import and shadow fleet to minimize the economic costs of the EU's sanctions. The major problem while preparing the thesis was the fact that Russia started using a shadow fleet which raised a question of reliance and accuracy of the economic data provided. Moreover, some of the selected Russian oil companies did not publish statistics after 2021. In addition, a more detailed assessment of the economic performance of the selected Russian oil companies could have been done, for instance, not only in relation to net profit and export volumes but also to stock prices and debt ratio.
Vedoucí práce: Ilya Bolotov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses